A novel laser diode wavelength stabilisation technique for use in high resolution spectroscopy - Asmari, Abdullah Shah (Cranfield University, 2015)
Tuneable diode laser absorption spectroscopy (TDLAS) based gas sensors are widely used for trace gas detection for their high selectivity and sensitivity. The laser source used in TDLAS requires a narrow line width in the order of 10s of MHz, with a wavelength stability multiple orders lower than the molecular absorption line width, which is, for example, 4.1GHz (38pm) for an air broadened methane line. TDLAS requires the use of a laser diode with a long term wavelength stability of better than 10% of the absorption line width of the target gas species. The wavelength stability of the laser is highly temperature dependent as the wavelength increases with increasing temperature. Therefore, control of the temperature of the laser diode is vital for stabilising the laser emission wavelength. In this thesis, a novel method has been proposed to measure and stabilise the temperature of a laser diode. The laser diode emission wavelength was stabilised by using its measured junction voltage in a control feedback loop. In order to determine the junction voltage, a series resistance correction term was identified, which was the novel part of this wavelength stabilisation technique. The laser diode junction and forward voltages were calculated from the forward voltage drop of the laser diode at measured at various operating temperatures. The laser diode series resistance was measured dynamically and was subtracted from the forward voltage to calculate the junction voltage. Both the forward voltage and series resistances were found to be temperature dependent. This method was investigated for its short term (~ 5minute) and long term (~ 1 hour) wavelength stability and was compared with other available methods. The laser diode wavelength stability attained using this method has been also investigated at various ambient temperatures (10-40 °C). ...[cont.]